Adoption Behaviour of Fish Farmers towards Better Management Practices (BMPs) of Seabass Farming - Himadri Prasad Jarh; Shyam Sundar Dana; Abdul Hannan Mondal; Moumita Ray (Indian Journal of Extension Education, 2024)
This study sought to assess the adoption behaviour of Better Management Practices (BMPs) in seabass farming among fish farmers in the Purba Medinipur district of West Bengal, India, in 2023 by constituting a randomly selected sample size of ninety from three purposefully chosen blocks in the district. It was found that a significant number of respondents were middle-aged (46.67%), had attained middle school education (46.67%), and had been farming for 6 to 10 years (60%). Most respondents (84.44%) reported seabass farming as their primary occupation and practiced it semi-intensively (77.78%). Adoption of Better Management Practices (BMPs) was moderate, with 61.11 percent of respondents showing a medium adoption level. Key practices, which were fully adopted by most of the respondents, included using lime to maintain water quality (90%), collecting seeds from reputable hatcheries or reliable wild seed collectors (85.6%), acclimatizing seeds before release (82.2%), maintaining size variation of seeds for polyculture to prevent cannibalism (81.1%). Eight variables, namely, age, education, annual income, farming area, experience, operation intensity, training attendance, and extension agency contact, were significantly correlated (p=<0.01) with BMP adoption.